Control of the spin in a tennis serve focusing on the motion of the upper limb and trunk - Murata, M.; Fujii, N. (International Journal of Sport & Health Science, 2022)
The purpose of this study was to investigate the relationship between motion and ball spin in tennis serves. Ten male university tennis players participated. The three-dimensional coordinates of the players performing flat, kick and slice serves were collected using a motion capture system with 8 cameras (250 Hz). Similarly, the three-dimensional coordinates of reflective markers on the ball were also collected (500 Hz). The primary variables computed were: racket face velocity and direction at impact, velocity and angular velocity of the ball after impact, hitting point, angles of the upper limb joints, and segment angles of the upper trunk. The differences in racket face velocity among flat, kick, and slice serves were divided into the following terms: 1) deltaVposture: A difference in velocity resulting from a change in upper trunk posture, 2) deltaVswing: A difference in velocity resulting from a change in arm swing (kinematics of the upper limb), 3) deltaVutrk: A difference in velocity resulting from a change in upper trunk translational and rotational motion. Repeated measures ANOVA ( p<.05) with Bonferroni multiple comparison was used to evaluate the effects of changes in form (with differences in ball spin) on each parameter. The findings are summarized as follows.